Correlation analysis of fluctuations in the serum interleukin-38, soluble RAGE and FIAF levels in prognosis of chronic obstructive pulmonary disease (COPD): Serum interleukin-38, soluble RAGE and FIAF levels in prognosis of COPD - Fu, Lu; Dou, Juanli; Ren, Boyu; Wang , Jing; Liu, Cong; Li, Binfeng (Journal of Medical Biochemistry, 2026)
[Objective] To explore the changes in the serum interleukin-38, soluble receptor for advanced glycation end products (soluble RAGE) and Fasting-Induced Adipose Factor (FIAF) levels in patients with chronic obstructive pulmonary disease (COPD) and to analyze their relationships with the severity and prognosis of the disease.[Methods] A total of 272 COPD patients admitted to the hospital from May 2023 to March 2025 were selected as the case group. Based on how quickly the condition progressed, the patients were split into two groups: those in the acute exacerbation stage (n=158) and those in the stable stage (n=114). An additional 176 healthy individuals who went to the hospital at that time for a physical checkup made up the control group. Serum FIAF, TLR4, soluble RAGE, and interleukin-38 levels were examined for each group, and the relationships between the above indicators and the severity and prognosis of the disease were analyzed.[Results] While soluble RAGE was lower in the acute exacerbation group than in the stable and control groups (P 1,172.53 ng/L, which are separate risk factors influencing COPD patients' prognosis.[Conclusion] Serum interleukin-38, soluble RAGE, TLR4 and FIAF levels in patients with COPD can reflect disease progression and can be used for prognosis assessment.
Keywords: Chronic obstructive pulmonary disease; Interleukin-38; Soluble receptor for advanced glycation end products; Toll-like receptor 4; Angiopoietin-like protein 4